XRF maps and line scans project files belonging to XRF instrument report. Identification of ink components through XRF analysis of Azzolino documents. - Marei Hacke (Swedish National Heritage Board, 2023)
RTX Project files. Details given in supporting information

S2 File. XRF instrument report.

Identification of ink components through XRF analysis of Azzolino documents.

https://doi.org/10.1371/journal.pone.0283539.s002

(DOCX)

Belonging to publication

Lagerqvist Alidoost A, Hacke M, Winther T, Sandström T (2023) A closer look at the Azzolino collection. PLOS ONE 18(4): e0283539. https://doi.org/10.1371/journal.pone.0283539
Keywords: iron gall ink; XRF; History and Archaeology; Historia och arkeologi